Cómputo de los caracteres irreducibles de las representaciones de Sn - Novoa Ramírez, Jesús Fernando; Departamento de Matemáticas Facultad de Ciencias Pontificia Universidad Javeriana, Bogotá (2003)
We implement the Roichman formula for computing the character table of the irreducible representations for the symmetric group. This formula unlike the Murnangham-Nakayama is not recursive